2017
DOI: 10.1021/acs.jced.7b00359
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction of Rhenium in Ionic Liquid with N235

Abstract: Extraction of rhenium into the ionic liquids phase from aqueous solutions was investigated using N235 as extractant. At temperatures from 293.15 to 318.15 K, the equilibrium molalities of ReO4 – were measured at an ionic strength from 0.2 to 2.0 mol·kg–1 in the aqueous phase containing NH4Cl as supporting electrolyte. The standard extraction constants K 0 at various temperatures were obtained by methods of the Pitzer polynomial approximation. Thermodynamic properties for the extraction process were calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…However, in that study, a phase modifier was also required. More recent studies using ILs as diluents used around 1% (w/w) of amine extractant (triisooctylamine) to obtain over 99% extraction of this metal ion from acid solutions 4,20 . In this work, only 3% (v/v) of [TOMA][BA] allows the extraction of around 95% of Re(VII) using an organic‐solvent‐free extracting solution without any phase modifier.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, in that study, a phase modifier was also required. More recent studies using ILs as diluents used around 1% (w/w) of amine extractant (triisooctylamine) to obtain over 99% extraction of this metal ion from acid solutions 4,20 . In this work, only 3% (v/v) of [TOMA][BA] allows the extraction of around 95% of Re(VII) using an organic‐solvent‐free extracting solution without any phase modifier.…”
Section: Resultsmentioning
confidence: 99%
“…More recent studies using ILs as diluents used around 1% (w/w) of amine extractant (triisooctylamine) to obtain over 99% extraction of this metal ion from acid solutions. 4,20 In this work, only 3% (v/v) of [TOMA][BA] allows the extraction of around 95% of Re(VII) using an organic-solvent-free extracting solution without any phase modifier. On the other hand, it has been also demonstrated that the use of ILs as diluents enhances the extraction percentages.…”
Section: Process Parameters Effect Of the Initial Phmentioning
confidence: 99%
See 3 more Smart Citations